An Analysis Of Educational Values In “Keluarga Cemara” Movie - Nurdini, Rahmi Aulia; Apriyanti, Fitri (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Finding the positive effects and educational values of watching movies for study was one of the study's main objectives.